Persistent fatigue in a female sprint cyclist after a talent-transfer initiative - Halson, S.; Martin, D. T.; Gardner, A. S.; Fallon, K.; Gulbin, J. (International Journal of Sports Physiology and Performance, 2006)
Heavy training loads combined with other life stressors and inappropriate recovery can lead to persistent fatigue in athletes.1 Mechanisms explaining the etiology of persistent fatigue in athletes (such athletes are often referred to as overtrained athletes) are available and frequently discussed in the scientific literature; howeve, documentation of athletes with persistent fatigue is rare.2 The majority of research examining persistent fatigue has focused on endurance athletes. We are unaware of research documenting persistent fatigue in athletes who specialize in events lasting less than 1 minute.3 To avoid confusion with other definitions of fatigue we have used the term persistent fatigue to describe the inability to perform a familiar exercise task, despite more than 3 weeks of recovery. The term persistent fatigue does not attribute cause to the condition (ie, inappropriate training, diet, or recovery) and reflects fatigue so severe that performance is lower than a baseline untrained level. We had a unique opportunity to monitor an athlete who experienced persistent fatigue after being introduced to sprint cycling. After developing fatigue, this cyclist moved to the Australian Institute of Sport (AIS) and was monitored by a multidisciplinary team including a medical doctor, a recovery specialist, a physiologist, a talent-identification specialist, a psychologist, a dietician, and a physiotherapist. the primary aims of this case study are to describe the conditions that preceded the development of persistent fatigue, outline the management approach for this fatigued athlete, and document the response to the recovery intervention.